Performance evaluation of bio l toilet waste digester technologies in Ghana: the ef cacy of ef uent treatment options - Amoah, Philip; Nartey, E. G.; Schrecongost, A. (Informa UK Limited, 2016)
The study was carried out to assess the ef cacy of a standard Bio l toilet digester with regard to its ef uentqualityandtoevaluatetheperformanceofnewef uentpolishingoptionsbeingdeveloped by Bio lCom. In uent and ef uent were collected from 18 standard Bio l digesters connected to full- ush toilets. Ef uent from ve pilot installations with improved ef uent polishing options were also taken for analyses. Ten other Bio l installations were selected to assess the impact of digester ef uent discharge on the surrounding soil. Pollutant concentrations in the Bio l ef uent exceeded both Ghana EPA and WHO standards for discharge though pollutant removal ef ciencies were high: 84% for biochemical oxygen demand, 86.1% for chemical oxygen demand and 82.4% for total suspended solids. Escherichia coli and total coliform levels were signi cantly reduced by 63% and 95.6%, respectively, and nutrients were the least removed from ef uents. Generally, ef uents from the majority of the pilot polishing options met most of the discharge standards. E. coli were present in the soil at all study sites, except one. Bio l digester ef uent is discharged subsurface but comparing their ef uent quality with standards for discharge into water courses is relevant especially in areas of frequent ooding and high water tables.